A Case Study of Chronic Kidney Disease - Vaishnav, Vijay; Ameta, Tarana; Sharma, Purushottam Das; Sharma, Dinesh Kumar; Deepa (International Research Journal of Ayurveda & Yoga, 2022)
Chronic Renal/Kidney Failure is another name for chronic kidney disease. Kidney illness is becoming more common in India as a result of changing lifestyles, dietary habits, hypertension, and uncontrolled diabetes. It is a silent assassin. Hemodialysis and peritoneal dialysis are the most common treatments for chronic kidney failure, followed by kidney transplantation. Kidney failure treatment is highly costly and out of reach for most Indians. Ayurveda has played an essential role in the early stages of renal failure in the hunt for this effective and safe treatment. A 35-year-old male patient with pitting edoema on his legs, eyes, and face, as well as dyspnea, frothy urine, anorexia, and constipation, is the subject of this case study. Chronic Kidney Disease has been diagnosed. Hemodialysis was recommended, but the patient refused, instead he had Ayurvedic treatment with Punarnava Mandur, Vrukkadoshantak Vati, Ark PunarnavaArk Makoe. Symptoms and investigation have improved. The purpose of this case study is to investigate Chronic Kidney Disease from an Ayurvedic perspective, as well as to examine the results of Ayurvedic therapy in Chronic Kidney Disease as a symptom and modern parameter investigation.